Transcriptional changes in ascorbate-glutathione cycle under drought conditions - Secenji, Mária; Bebes, Attila; Hideg, Éva; Györgyey, János (Acta Biologica Szegediensis, 2008)
Ascorbate-glutathione cycle has an important role in defensive processes against oxidative damage generated by drought stress. Changes in expression patterns, subjected to reduced amount of irrigation solution, of ascorbate peroxidase (APX), monodehydroascorbate reductase (MDAR) and dehydroascorbate reductase (DHAR) as enzyme families of this cycle were studied comparing a drought tolerant (Triticum aestivum cv. Plainsman V) and a drought sensitive (Triticum aestivum cv. Cappelle Desprez) wheat genotype. Relative transcript level of isoenzymes localized in distinct subcellular organelles showed significant differences between the two genotypes at the beginning of treatment. Among APX isoenzymes, a thylakoid-bound (tAPX), two stromal (sAPX1, sAPX2), one of the two cytosolic (cAPX1) and a peroxisomal (mAPX) APXs displayed higher relative transcript level in the drought tolerant genotype. The same was observed in case of cytosolic (cDHAR) and stromal (sDHAR) DHARs. However, relative transcript levels of MDHAR isoenzymes were similar in both genotypes. Under drought conditions, the initial relative transcript levels of distinct isoenzymes changed differently comparing the two genotypes leading to the final conclusion that the drought tolerant genotype up-regulates mostly the cytosolic APXs and MDARs to maintain the cellular ascorbate redox state, however in the drought sensitive genotype, sAPX and sDHAR are induced to fill the same function.